2013
DOI: 10.4238/2013.may.13.10
|View full text |Cite
|
Sign up to set email alerts
|

HuGE systematic review and meta-analysis demonstrate association of CASP-3 and CASP-7 genetic polymorphisms with cancer risk

Abstract: ABSTRACT. Genetic variations in the caspase genes CASP-3 and CASP-7 are known to be involved in apoptosis, cytokine maturation, cell growth and differentiation. Polymorphisms of CASP-3 and CASP-7 genes have been increasingly recognized as important regulators in the development of cancer. However, whether there is a specific association is still controversial. Therefore, we made a Human Genome Epidemiology review and meta-analysis to explore the association between polymorphisms of CASP-3 and CASP-7 genes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…By calculating the numbers of the high-risk genotype, we found that the risk of NIHL in those carrying two risk genotypes was 1.787-fold higher than in those carrying no risk genotype (OR = 1.787, 95%CI = 1.104–2.892). This is similar to the results of Yan et al [20]. By the stratified analysis, positive results were only founded when noise intensity was <85 dB(A) or CNE < 90 dB(A), and the effects of high-risk genotype were not observed when noise intensity was ≥85 dB(A) or CNE ≥90 dB(A).…”
Section: Discussionsupporting
confidence: 90%
“…By calculating the numbers of the high-risk genotype, we found that the risk of NIHL in those carrying two risk genotypes was 1.787-fold higher than in those carrying no risk genotype (OR = 1.787, 95%CI = 1.104–2.892). This is similar to the results of Yan et al [20]. By the stratified analysis, positive results were only founded when noise intensity was <85 dB(A) or CNE < 90 dB(A), and the effects of high-risk genotype were not observed when noise intensity was ≥85 dB(A) or CNE ≥90 dB(A).…”
Section: Discussionsupporting
confidence: 90%
“…As an effector CASP, CASP3 plays an important role in the execution phase of apoptosis, also in the development and progression of cancers [1617]. Several previous studies have shown associations of CASP3 polymorphisms on the risk of different types of cancer, including HCC [13, 1820]. Moreover, studies in several tumor types indicated that the expression levels of CASP3 have effects on the development and survival of cancers [8, 17, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Human Genome Epidemiology review and meta-analysis polymorphisms of CASP3 and CASP7 genes were found to be linked to cancer risk. 151 Although somatic CASP3 mutations are rare in most tumors, 152 CASP3-variant alleles have been detected in squamous cell carcinomas of the head and neck (SCCHN) and associated with increased risk of SCCHN. 153 In addition, CASP3-variant alleles are associated with risk of endometrial cancer 154 and NHL 155 and multiple myeloma.…”
Section: Caspases In Tumorigenesismentioning
confidence: 99%